Fissures of the frontal operculum in as a South African sample - Kamanzi-wa, Sylvia (My University, 2006)
This study primarily seeks to confirm two systems of classifying the sulci of the frontal operculum1 (F3): the radiologically derived system of Ebeling et al (1989) involving four Types of Sulcal Connections, and the anatomical classification of the anterior rami of the lateral fissure, involving three patterns. Sulcal- and intersulcal- lengths are also considered. The sample consisted of 220 cadaveric hemispheres; 65 of which were whole brains (control category); and 90 consisting of equal numbers of separate right- and lefthemispheres (case category). Specimens were orientated by examining relevant features of: the lateral fissure; the postcentral sulcus; and the central fissure. Features of the remaining boundary sulci (precentral sulcus / sulci, and inferior frontal sulcus) of F3 were also considered. The focus was on examining the: frequency of occurrence, shape, and connections of the sulci of the F3. The sulci of F3 were designated as: major sulci [anterior ascending (AAR)- and anterior horizontal (AHR)- rami, and stem of the anterior rami when present); and accessory sulci (sulci of the –pars opercularis and –pars triangularis). Sulcal lengths were measured using thread, with needles as anchors. Intersulcal lengths were recorded as straight-line distances between parallel pins inserted into the sulci of the frontoparietal operculum. Specimens fixed outside the cranial cavity were excluded from measurement. The reliability of the data was monitored, by repeating the observations. The two systems of classification were broadly confirmed. The criteria for the Types of Sulcal Connections were modified in view of the findings on double precentral sulci and the connections of the opercular sulcus (which occurred as either one or as two sulci). A sulcus of the pars triangularis (which occurred as either one, two, or as three sulci) was found to be a useful landmark. The Chi-square test was applied to the data in the two systems of classification. There were no significant interhemispheric differences with respect to the incidences of: Types 1-4 of Sulcal Connections, or Patterns of the Anterior Rami (I, Y, and VU). Sulcal lengths were similar to that reported by Ono et al (1990). The Student t-test was applied to sample sizes 18 and above. No significant interhemispheric differences, in the lengths of the sulci that were considered, were found. A significant 1 The definition of the frontal operculum as the inferior frontal gyrus only, is used for the purposes of this study. The frontal operculum may also be abbreviated as F3. v difference was found in two instances when comparing the case- and control- categories. Intersulcal distances are reported on in the frontal- and frontoparietal- operculum.
Faculty of Sciences School of Anatomical Sciences 0202721m slyviakamanzi@yahoo.com
Keywords: Frontal Operculum; Anterior; Daigonal; Triangular; sulcus